Prediction of Mefenamic Acid Solubility and Molecular Interaction Energies in Different Classes of Organic Solvents and Water - Siti Kholijah, Abdul Mudalip; Fatmawati, Adam; Mohd Rushdi, Abu Bakar; Parveen, Jamal (2018)
Solubility of a targeted compound as a function of temperatures or solvent compositions is essential in designing pharmaceutical crystallization process [1, 2]. Due to that, fast determination of solubility data either through experimental or model based approaches becomes a necessity. Mefenamic acid (2-[(2,3-dimethylphenyl)amino]benzoic acid, C15H15NO2) is extensively used for control of pain due to menstrual disorder and as anti-proliferative agents [3]. Conductor-like Screening Model for Real Solvents (COSMO-RS) is an alternative method for prediction of thermodynamics properties of fluids based on the molecular charge density that obtained by molecular quantum chemical calculation (COSMO) [4]. The aim of this work is to predict and investigate the solubility of mefenamic acid as a function of solvent types and temperatures using COSMO-RS. The solvents studied in this work were divided into three groups. Group 1 comprises of dipolar aprotic solvents (N, N-dimethylacetamide (DMA), N, N-dimethylformamide (DMF), acetone and ethyl acetate). Group 2 consist of polar protic solvents (ethanol, propan-2-ol, and water). Group 3 consist of apolar aprotic solvents (hexane, heptane, and cyclohexane). The temperatures were varied from 298 K to 323 K. The mefenamic acid show high solubility in solvent form Group 1, moderate in Group 2, except water and poor in Group 3. As illustrated in Fig. 1, the predicted solubility values using COSMO-RS concur very well with the experimental values obtained from literature [5] with an average mean relative errors (mse) less than 0.02. The predicted solubility also increase with the increase of the temperature. The calculated Gibbs free energy change of mefenamic acid in the solvents studied also agreed with the solubility data. The increase of solubility with the increase in temperature is probably due to the increase in molecules’ kinetic energy at higher temperatures that leads to more effective movement or interactions between solvents with the solute molecules. Moreover, the heat adsorbed at high temperature facilitate the dissolution of solute compound by breaking the bonds in the solute molecules [6]. The predicted microscopic interaction energies, namely misfit (H-MF), hydrogen bonding (H-HB), and van der Waals (H-vdW) show small increment in the energies values as the temperature increases. The changes of H-HB energy in different solvents are more significant than H-vdW and H-MF (See Fig. 2). This findings may suggest that the H-HB interactions between mefenamic acid and solution are significantly contribute to the differences in the mefenamic acid solubility.